Pattern of Ligature Mark in Cases of Compressed Neck in Rajkot Region: A Prospective Study - Momin, Sadikhusen G; Mangal, Hari Mohan; Kyada, Hetal C; Vijapura, M T; Bhuva , S D (Journal of Indian Academy of Forensic Medicine, 2012)
Ligature mark may be the only evidence available in cases of asphyxial deaths due to either  hanging or strangulation. A through examination of the ligature mark and analysis of the information  provided by it is therefore, a must to arrive at the most probable cause of death and differentiate between  hanging and the ligature strangulation. A prospective study was conducted at the Department of Forensic  Medicine, P.D.U. Medical College & Hospital, Rajkot from January 2008 to December 2008. During that  period out of 2159 cases, 90 cases of hanging and 7 cases of ligature strangulation were selected for the  present study. We found that deaths due to hanging constituted 4.17% of the total unnatural deaths  subjected to medicolegal autopsy; young adults of the age group 21 to 30 years accounted for the  maximum cases 40% and the male: female ratio was 2:1. Chunni (34.44%) was the most common  ligature material used. The mark was obliquely placed (100% cases) above thyroid cartilage (80% cases).  In all the cases of ligature strangulation the mark was transverse and below the level of thyroid cartilage.
Keywords: Hanging; Ligature strangulation; Ligature mark